Hijab in the city: Discursive representation of female modesty in selected contemporary Malaysian media / Nurzihan Hassim - Nurzihan, Hassim (2017)
The purpose of this study is to explore the evolving cultural identity of Malay-Muslim women through the hijab; or the act of veiling, from discursive representation of female modesty in Malaysian media. At present, women in many Muslim-majority countries are embracing the hijab as a public symbol of their faith, thus, establishing the garment as a form of worship. Furthermore, the hijab conveyed solidarity against Islamophobia after 9/11 and is symbolic in renouncing Western imperialism in social, political and economic developments. However, scholars argued that the globalization of Islam had commodified the hijab and objectified veiled women for fashion in mainstream Malaysian media (Hochel, 2013; Wok & Mohd, 2008). This phenomenon is reinforced by conversations of the hijab in social media sphere that connect like-minded audiences. As a result, modern representations of the hijab is observed to have shifted the focus of religiosity of the hijab towards the push of Islamic cosmopolitanism and produced constructs for cultural and material consumption for Malay-Muslim women who wear them. This study explored the role of selected contemporary media in renewing public practices of the hijab through displays of liberated, Islamic womanhood by Malay-Muslims. The works of Katz, Blumler and Gurevitch (1974) on Uses and Gratifications are drawn upon as a foundation to explore patterns of hijab representation in media, followed by the postmodern Double Bind Theory to examine negotiations of hijab practice from the media user perspective; in addition to Giddensï¿½ duality of structure (1984) that discussed systemic patterns of change through assimilation of the hijab as an identifier of ï¿½Malay-Muslimnessï¿½. Further to this, the study conducted analyses on Malay lifestyle magazines Hijabista, EH! and Wanita to examine hijab-wearing discourse in contemporary media content. Secondly,social media conversations on entertainment blog; Beautiful Nara, were examined to understand how Malaysian audiences negotiate the meanings of the hijab presented to them. Thirdly, data was gathered from an online opinion column written by journalist Dina Zaman, followed by interviews with media practitioners to analyze the permeation of hijab culture as an identity for Malay-Muslims. Findings of this study suggested that the hijab phenomenon had shaped an egalitarian Malay-Muslim structure that is adaptive to Islamic cosmopolitanism. The research questions lead to how selected contemporary media created awareness and appreciation of the hijab among educated, affluent and urban media audiences. Full control of their knowledge consumption is achieved when they are selective of their participation in the public discourse of hijab. Aside from empowerment, agency of communal experience within the media sphere saw relatability of role models that validated the practice of hijab for Malaysian media consumers. Additionally, their sense of belonging as well as differentiation in a vast, multi-ethnic society contributed to the growing share of hijab voices in media, encouraging transnational opportunities of a unique, Malaysian subculture that are mediated by global media flows of Islam.